Hypoxic modulation of exogenous nitrite-induced vasodilation in humans. - Maher, A; Milsom, AB; Gunaruwan, P; Abozguia, K; Ahmed, I; Weaver, R; Thomas, P; Ashrafian, H; Born, G; James, P; Frenneaux, M (2008)
BACKGROUND: It has been proposed that under hypoxic conditions, nitrite may release nitric oxide, which causes potent vasodilation. We hypothesized that nitrite would have a greater dilator effect in capacitance than in resistance vessels because of lower oxygen tension and that resistance-vessel dilation should become more pronounced during hypoxemia. The effect of intra-arterial infusion of nitrite on forearm blood flow and forearm venous volumes was assessed during normoxia and hypoxia. METHODS AND RESULTS: Forty healthy volunteers were studied. After baseline infusion of 0.9% saline, sodium nitrite was infused at incremental doses from 40 nmol/min to 7.84 mumol/min. At each stage, forearm blood flow was measured by strain-gauge plethysmography. Forearm venous volume was assessed by radionuclide plethysmography. Changes in forearm blood flow and forearm venous volume in the infused arm were corrected for those in the control arm. The peak percentage of venodilation during normoxia was 35.8+/-3.4% (mean+/-SEM) at 7.84 micromol/min (P<0.001) and was similar during hypoxia. In normoxia, arterial blood flow, assessed by the forearm blood flow ratio, increased from 1.04+/-0.09 (baseline) to 1.62+/-0.18 (nitrite; P<0.05) versus 1.07+/-0.09 (baseline) to 2.37+/-0.15 (nitrite; P<0.005) during hypoxia. This result was recapitulated in vitro in vascular rings. CONCLUSIONS: Nitrite is a potent venodilator in normoxia and hypoxia. Arteries are modestly affected in normoxia but potently dilated in hypoxia, which suggests the important phenomenon of hypoxic augmentation of nitrite-mediated vasodilation in vivo. The use of nitrite as a selective arterial vasodilator in ischemic territories and as a potent venodilator in heart failure has therapeutic implications.